Execuç\~ao do Programa de Aquisiç\~ao de Alimentos nos municípios brasileiros - Regina Helena Rosa Sambuichi; Ana Flávia Cordeiro de Almeida; Gabriela Perin; Iracema Ferreira de Moura; Paulo Sergio Cândido Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Intended to encourage family farming and promote food and nutritional security, the Food Acquisition Program - PAA purchases products directly from family farmers and their organizations to attend population in situation of vulnerability through the do nation of these foods. This study did a quantitative analysis of the implementation of PAA in the period from 2011 to 2018, seeking, mainly, to identify factors related to the access of the municipalities to the program, in addition to analyzing its focalization and potentialities to assist in facing the challenges that arise nowadays. The results showed that the program benefited more than 450 thousand family farmers in the period, purchasing 2 million tons of food and reaching beneficiaries in about 83% of Brazilian municipalities. The probability of access was greater for municipalities with less economic development, less urban, with more family farmers and belonging to the North and Northeast regions, indicating that the program is being effective in its focalization in attending the poorest regions of rural development as a priority. These data corroborate the studies found in the literature that point to PAA as an important commercialization channel for family farming, capable of promoting increased income, productive inclusion and the dynamization of the local economy, in addition to contributing to food and nutritional security. Thus, it is believed that the program is a relevant tool to be used as an instrument to mitigate negative effects in the economic and social spheres generated by the current crises. However, there was a significant decrease in the resources applied in PAA in recent years, which is worrying, considering its recognized relevance and ability to generate benefits. Therefore, it reinforces the need to expand the investment of resources in the program, in this and in the coming years, in order to ensure that it can achieve its goals and act appropriately in the fight against current challenges.
Keywords: Q18; 330; family agriculture; public policies; food security and nutrition